Cadera, S. M., & Walsh, A. S. (Eds.). (2022). Retranslation and Reception: Studies in a European Context (Vol. 49). Brill. - Luomei Cui (Cadernos de Tradução, 2025)
Book review: Retranslation and Reception: Studies in a European Context.